RELIABILITAS DAN VALIDITAS SELF-COMPASSION SCALE VERSI BAHASA INDONESIA - Sugianto, Dicky; Suwartono, Christiany; Sutanto, Sandra Handayani (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology)
Abstract ? Self-compassion is a healthy attitude toward oneself which positively associated to an individual?s mental health. Self-Compassion Scale (SCS) is a common instrument to measure levels of self-compassion However, to date, there is no study that evaluates the psychometric properties of the Indonesian version of SCS. This study aims to adapt the SCS into Indonesian language and to evaluate the psychometric properties of the Indonesian version of SCS. Participants in this study were 329 college students enrolled in universities in Jakarta and surrounding areas and were recruited through convenience sampling. Instrument used in this research is the Indonesian version of SCS, which we named Skala Welas Diri (SWD). The result of psychometric evaluation using confirmatory factor analysis (CFA), construct validity, and Cronbach?s Alpha coefficient showed good validity and reliability of SWD. The study suggested that SWD have a similar theoretical model as SCS. The study concludes that SWD could be used as an adequate measurement of self-compassion.Abstrak ? Welas diri (self-compassion) merupakan sebuah sikap yang sehat terhadap diri dan berkaitan dengan kesehatan mental. Self-Compassion Scale (SCS) merupakan instrumen yang umum digunakan untuk mengukur welas diri, tetapi belum ada penelitian yang melihat kualitas psikometrik dari adaptasi SCS Bahasa Indonesia. Penelitian ini bertujuan untuk melakukan adaptasi dan uji psikometrik SCS Bahasa Indonesia. Partisipan dalam penelitian ini adalah 329 mahasiswa aktif di salah satu universitas di Jakarta dan sekitarnya yang direkrut dengan convenience sampling. Instrumen yang digunakan adalah SCS yang diadaptasi ke dalam Bahasa Indonesia dan diberi nama Skala Welas Diri (SWD). Berdasarkan hasil uji psikometrik menggunakan confirmatory factor analysis (CFA), uji validitas konstruk, dan koefisien Cronbach?s Alpha, ditemukan bahwa SWD memiliki validitas dan reliabilitas yang baik, serta memiliki model teoretik yang sama dengan SCS. Disimpulkan bahwa SWD dapat digunakan sebagai skala yang mumpuni untuk mengukur welas diri.